Affordances and challenges of teaching language skills by virtual reality: A systematic review (2010–2020) - Bahari, Akbar (E-learning and digital media, 2022)
The emergence of newer educational technologies provides opportunities for computer-assisted language learning practitioners and software developers to capitalize on the affordances for the second language (L2) learning purposes. This article explored and brought together the reported affordances and challenges of virtual reality to teach the L2 receptive and productive skills by reviewing seventy-five peer-reviewed articles published from 2010 to 2020. The results revealed an imbalanced trend of research on language skills learning by virtual reality tools and affordances in favor of listening and speaking skills compared to reading and writing skills. The obtained data were tabularized in terms of language skills. The results were visualized by hierarchical database formats. Pedagogical implications of the study inform teachers about affordances available to teach L2 skills in educational virtual reality environments toward a more digitally enhanced L2 pedagogy. Theoretical implications of the study inform researchers about the challenges that need to be addressed.